The Effect of Environmental Tax - Spending Mix on Province Air Quality - Qibthiyyah, Riatu Mariatul; Zen, Fauziah (Signifikan: Jurnal Ilmu Ekonomi, 2023)
The provincial government in Indonesia has been mandated to collect environmental-related taxes in recurrent vehicle taxes, vehicle transfer taxes, and gasoline taxes. These vehicle-related taxes have been the dominant type for the provincial government. Yet, the environment-related spending has been relatively low, within 1-3% of total expenditures. This study examines to what extent such environmental tax–spending mix affects the environmental outcomes measured by the air quality index. The novelty of this study comes in using detailed environmental-related tax revenues at the sub-national level and providing a context of the large developing country in a decentralized economy – Indonesia – as a case study. Our study finds the link between environmental tax in the case of the vehicle recurrent tax and gasoline tax in improving air quality and environmental quality index, respectively. But on the spending side, there is no evidence that provincial environmental spending may improve the air or environmental quality index. Nonetheless, we found a correlation between the vehicle transfer tax revenues and the share of province environmental spending, implying that environmental tax revenues, to some extent, correspond to the related provincial expenditures on environmental protection. This study signals the need also to expand environmental spending to complement existing environmental tax policy at the provincial level.JEL Classification: H71, H76, Q53How to Cite:Qibthiyyah, R. M., & Zen, F. (2023). The Effect of Environmental Tax Spending Mix on Province Air Quality Index. Signifikan: Jurnal Ilmu Ekonomi, 12(2), 221-230. https://doi.org/10.15408/sjie.v12i2.32395.